Leucaena (Leucocephala- Lam De Wit) una leguminosa promisoria para Colombia - Sánchez Neira, Pedro (1983)
The plant LEUCAENA (Leucaena leucocephala) is a legume very promissory for the Colombian tropical zones like: combustible, forage`s productive, wood, land`s improvement, erosion`s control, stabilizer of bell of a water and human`s food. Several farmers and pertaining to cattle, specially in Tolima`s and Huila`s Departments, in the last three years begin to be interested in this plant that nowadays have special importance in Australia, Phillippines, Haitf and Hawaii. Scientific Entities like CSIRO in Australia, Hawaii`s and Manoa`s Universities in the United States of North America, CIAT in Colombia come to advancing labors of special interested. It also has particular importance the works, referring to LEUCAENA, progressed by the Agency for International Development in Haití